Intoxicação aguda por agrotóxicos em agricultores: comparação entre os métodos de dosagem da colinesterase e de análise por micronúcleo - Klein, Marcieli Schlotefeldt (2020)
Brazil has a high consumption of pesticides and the State of Rio Grande do Sul has the third most sales of pesticides. Rural workers are exposed directly to pesticides since the management of pesticides is part of their work activity. The study aimed to compare two methods to detect acute pesticide intoxication in farmers: cholinesterase measurement and micronucleus analysis. The research was both quantitative and comparative. Two study groups were defined, an exposed group and a group not exposed to pesticides. Male rural workers, aged between 18 and 59 years, non smokers, and non-alcoholics, who work at least 15 hours per week in agricultural activities using pesticides were selected for the exposed group. The control group was composed of 27 individuals with same characteristics; however, they live in urban areas and do not use pesticides. Each research participant had blood collected in a laboratory located in their city of residency. The blood was analyzed for erythrocyte and plasma cholinesterase as well as other blood tests. In the exposed group, two collections were carried out, one after the application of insecticides and the other after the application of a non-insecticide pesticide. The same blood examinations were performed in the unexposed group only once. Statistical analysis was performed using R software (v. 3.6.3) and considered a significance level of 5%. Results showed that the exposed group had a higher prevalence of micronuclei when compared with individuals in the group not exposed to pesticides. The values for the erythrocyte and plasma cholinesterase tests did not show any significant difference between the groups. Finally, a need to change the Regulatory Norm 31 (NR 31) on health and safety at work in agriculture, livestock, forestry, logging, and aquaculture is observed. Furthermore, discussions of public policies to effectively monitor rural workers exposed directly to pesticides should be encouraged.